Poldip2 knockdown protects against lipopolysaccharide-induced acute lung injury via Nox4/Nrf2/NF-κB signaling pathway - Wang, Yueguo; Wang, Wenwen; Zhou, Shusheng; Wang, Yulan; Cudjoe, Obed; Cha, Yu; Wang, Chunyan; Cao, Xiaoguang; Liu, Wei; Jin, Kui (Frontiers in Pharmacology, 2022)
Polymerase δ-interacting protein 2 (Poldip2) has been reported to mediate acute lung injury (ALI); however, the underlying mechanism is not fully explored. Male C57BL/6 mice and A549 cells were used to establish the lipopolysaccharide (LPS)-induced ALI model, then the expression of Poldip2 and its effect on oxidative stress and the resulting inflammation were detected. Adeno-associated virus serotype 6 (AAV6) mediated Poldip2 knockdown was transfected into mice via intratracheal atomization. And A549 cells stimulated with LPS was used to further confirm our hypothesis in vitro. ML385, specifically inhibited the activation of the Nrf2 signaling pathway. Our data suggested that LPS stimulation remarkably increased protein levels of Nox4 and p-P65, activities of NADPH and MPO, and generation of ROS, TNF-α, and IL-1β while decreased protein levels of Nrf2 and HO-1 compared with those in NC shRNA+Saline group, which were obviously reversed by Poldip2 knockdown. Concomitantly, Poldip2 knockdown dramatically reduced contents of MDA and enhanced activities of SOD and GSH-Px compared to NC shRNA+LPS group. In vitro, we found that knockdown of Poldip2 significantly reversed LPS-induced increase protein levels of Nox4 and p-P65, activity of NADPH, and generation of ROS, TNF-α, and IL-1β, and decrease protein levels of Nrf2 and HO-1, ML385 pretreatment reversed the effects of Poldip2 knockdown mentioned above. Our study indicated that Poldip2 knockdown alleviates LPS-induced ALI via inhibiting Nox4/Nrf2/NF-κB signaling pathway.